Implementation of Divorce Lawsuit in Religious Court Reviewed from Madhhab Shafi'i (Study of the Decision of the Binjai Religious Court No. 258/Pdt.G/2016/P.A.Bji.) - Hasan Munthe; Azzahrawani Syakira (ISNU Sumatera Utara, 2025)
Khulu' is a way out provided by religion for women to break free from the bonds of marriage in exchange for the payment of ransom to their husbands. In fiqh literature, divorce lawsuits without iwadh are not known, while in laws and regulations there is the concept of a divorce lawsuit without ransom. This research is a juridical normative research. The results of this study show that there is a difference in the concept of divorce lawsuits between the Shafi'i school and the Binjai Religious Court Decision due to a difference in concept. In the Shafi'i mazahb it is stipulated that Talak is the absolute right of the husband and if the Talak is requested (sued) by the wife, then the wife is obliged to pay the ransom (iwadh) to the husband. Meanwhile, in the applicable laws and regulations in Indonesia, wives are given the right to divorce their husbands without having to provide iwadh.